Penerapan Pendekatan STEM Dalam Meningkatkan Keterampilan Proses Sains Sekolah Dasar - M. Pandi Mazlan Pandi; Muhammad Nur Wangid; Dita Afianti (Postgraduate, University of Mataram, 2024)
Science process skills are one of the important skills that students must have. This is because it can improve students' basic competencies, which include the formation of scientific attitudes, as well as their ability to solve problems. The STEM (Science, Technology, Engineering, Mathematics) approach is considered capable of encouraging students to improve these skills and solve problems in an integrated manner from an early age. This is because STEM is an approach that integrates science, technology, engineering and mathematics into one learning process, so that it will focus students on solving problems related to everyday life. The purpose of this article is to examine how the application of the STEM approach improves students' science process skills. The method used in this article is a systematic literature review. Literature reviews are carried out by analyzing various references related to the research topic. Data collection was carried out by following the PRISMA guidelines sourced from two databases, namely Google Scholar and Scopus, with a time span of 2015–2024 through the assistance of the Publish or Perish 8 (PoP) application. A total of 15 articles were obtained which were used as research data that were analyzed. The results of this study concluded that the application of the STEM approach can improve students' science process skills positively. Furthermore, teachers must be able to improve their skills in applying this STEM approach in teaching and learning activities in the classroom.